(untitled) (International Journal of Advanced Research in Computer Science, 2017)
VANET is different from MANET due to high mobility of nodes and large scale networks. VANET is a form of network that provide vehicle to vehicle and vehicle to infrastructure communication. The main gaol of VANET is to provide the road safety .Various wireless communication technologies used for VANET, the IEEE 802.11p is to support the medium range communication characteristics of vehicular environments. One of the main issues of VANET is handover process. It can be effectively achieved through Fast Handover for IEEE 802.11p (FHP) mechanisms and it is based on vehicle to infrastructure communications. FHP is proposed for efficient data transmission that takes place high mobility of vehicles and continuous topology change. The performance evaluation and simulation results show that the scheme can minimize the handover latency and packet loss. Keywords: VANET, Handover, IEEE82.11p,FHP, latency, packet loss